In vitro-screening of three Potato(Solanum tuberosum L) varieties for salt stress tolerance - مصا ريما; البيسكي فهد (Latakia University Journal -Biological Sciences Series, 2022)
This research was carried out in the laboratories of the National Commission for Biotechnology (NCBT) and the Faculty of Agriculture (Damascus/Syria) during the years 2019- 2020. It aimed to study the effect of salt stress on some growth parameters (stem length and diameter, leaf area, number of leaves, root length as well as wet and dry weight).of three Potato varieties (Arizona, Sifra and Dimant). the study used arandomized complete block design, the study included four concentrations of NaCl (50, 100,150 and 200 mM) in addition to the control (without NaCl). The results showed that the addition of NaCl to the growth medium had a negative effect the growth parameters in every variety (Arizona, Sifra and Dimant), The treatment of the control was significantly outperformed all the studied treatments in terms of the leaf area (13.63, 11.81, ، 9.81 cm2/plantlets, respectively), stem length (18.62, 16.97, 10.70 cm, respectively), wet weight (4.57, 3.73, 2.56 g, respectively) and dry weight (2.01, 1.08, 0.93 g, respectively ). the Varity Arizona is excelled on varieties Sifra and Dimant in most of growth parameters under salt stress conditions in vitro.